Biomass and total carbon in oak forests of Southern Colombian Andes: contributions to the REDD+ project-wide approach. - Yepes, Adriana (2016)
Carbon estimations in tropical forests are very important to understand the role of these ecosystems in the carbon cycle, and to support decisions and the formulation of mitigation and adaptive strategies to reduce the greenhouse emission gases (GHG). Nevertheless, detailed ground-based quantifications of total carbon stocks in tropical montane forests are limited, despite their high value in science and ecosystem management (e.g. REDD+). The objective was to identify the role of these ecosystems as carbon stocks, to evaluate the contribution of the pools analyzed (aboveground biomass, belowground biomass and necromass), and to make contributions to the REDD+ approach from the project scale. For this study, we established 44 plots in a heterogeneous landscape composed by old-grown forests located in the Southern Colombian Andes. In each plot, all trees, palms and ferns with diameter (D) ≥ 15 cm were measured. In the case of palms, the height was measured for 40 % of the individuals, following the Colombia National Protocol to estimate biomass and carbon in natural forests. National allometric equations were used to estimate aboveground biomass, and a global equation proposed by IPCC was used for belowground biomass estimation; besides, palms’ aboveground biomass was estimated using a local model. The necromass was estimated for dead standing trees and the gross debris. In the latter case, the length and diameters of the extremes in the pieces were measured. Samples for wood density estimations were collected in the field and analyzed in the laboratory. The mean total carbon stock was estimated as 545.9 ± 84.1 Mg/ha (± S.E.). The aboveground biomass contributed with 72.5 %, the belowground biomass with 13.6 %, and the necromass with 13.9 %. The main conclusion is that montane tropical forests store a huge amount of carbon, similar to low land tropical forests. In addition, the study found that the inclusion of other pools could contribute with more than 20 % to total carbon storage, indicating that estimates that only include the aboveground biomass, largely underestimate carbon stocks in tropical forest ecosystems. These results support the importance of including other carbon pools in REDD+ initiatives’ estimations.